(untitled) (Olhar de Professor, 2022)
This paper presents a version on higher education in the scenario of the of the Federal Institute of Education, Science and Technology of São Paulo (IFSP), discussing the elitist bias of the trajectory of this level of education in Brazil. Based on the documentary research on the Institutes Creation Law and the Institutional Development Plan (PDI), analyses were made about teacher training beacons (FOR-20) and technical courses (TEC-50). Further, the studies have turned to the Other category, which is not provided for by the Law of Creation of Institutes, but which is strongly present in the modalities of courses offered in the campuses of the IFSP. With a quali-quantitative approach, strong results were obtained that ifsp campuses extrapolate to the maximum percentage established by exclusion. With the documentary analysis made during the research, it was possible to notice that the campuses do not need to offer courses in the Other modality, but rather to fulfill the minimum of 70% of the vacancies for the FOR-20 and TEC-50 beacons provided for by law, emphasizing that the extrapolation of the other category directly impairs the offer of vacancies for the degrees and / or technical courses. With the extrapolation of this modality (Other), a category that prioritizes the implementation of elitist courses, it was possible to portray that elitization is present in the IFSP. Furthermore, it should be noted that the extrapolation of the Other category directly impairs the offer of vacancies for bachelor’s and/or technical courses.